Cinema, educação e filosofia: possibilidades de uma poética no ensino - Angerami, Paula Linhares [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cinema has been used in education, although in an instrumental way, as a didactic resource to reach a previously determined educational aim. This research will analyze the possibility of utilizing for education the esthetic qualities provided by cinema. Specifically, I will explore the possibility of teachers using selected films to provide to students a unique visual and auditory opportunity to observe and discuss a particular qualitative and reflective experience, along the lines recommended by Dewey. In order to accomplish this, I will discuss cinema as a component of the poetic of education, approaching the intellectual, moral, esthetical and ethical aspects of human beings. In that perspective, through the hermeneutic method, I will analyze and conceptualize esthetic, qualitative experience and reflective thought using Dewey as a reference. Following this, I will discuss in depth the concept cinema The expected result is to verify the potentiality of cinema to provide a first quality qualitative and reflective experience about ethic’s questions.

O cinema é utilizado na educação, mas como recurso didático para atingir um objetivo educacional previamente determinado. Esta pesquisa tem como objetivo analisar as possibilidades de se recorrer ao cinema na educação, em razão de suas qualidades estéticas, mais especificamente em virtude da possibilidade de apropriação de determinadas obras cinematográficas por parte de professores, de modo a lhes proporcionar uma experiência qualitativa e reflexiva nos termos assinados por John Dewey. Para tal, abordaremos o cinema como parte de uma poética educacional que, indo além dos aspectos intelectuais, procura integrar os aspectos morais, éticos e estéticos do ser humano. Dessa perspectiva, por intermédio do método hermenêutico, analisaremos conceitualmente a estética, experiência qualitativa e pensamento reflexivo, tomando como referencial teórico a obra de Dewey. Concomitantemente, discutiremos a concepção de cinema estabelecendo relações com a análise do pensamento deweyano. Assim, verificaremos as potencialidades do cinema para alcançar uma experiência qualitativa e reflexiva sobre questões éticas.
Keywords: Dewey, John 1859-1952; Cinema na educação; Estética; Filosofia; Ética; Education